Severe, Infantile-Onset Seizure Pattern in Sturge-Weber Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Researchers at the Hunter Nelson Sturge-Weber Center, Kennedy Krieger Institute, Baltimore, reviewed the records of 100 consecutive children and adults with confirmed Sturge-Weber syndrome (SWS) to determine the nature and prognosis of associated seizures.